Estrategias psicopedagógicas basada en la lúdica para disminuir los problemas de la disgrafía de una estudiante de quinto grado de la Unidad Educativa Fiscomisional Educare, período 2022-2023 - Saca Patiño, Luis Andres (2023)
The curricular integration work had as objective: to develop a psycho-pedagogical strategy based on play to reduce the problems of dysgraphia of a fifth-grade student of the Educare Fiscomisional Educational Unit, period 2022-2023. The quantitative approach for the methodology was considered, with a case study design, descriptive and cross-sectional. For the collection of information, a variety of techniques such as observation, record sheets, and achievement sheets were used. Regarding the instruments, the psycho-pedagogical file and the respective evaluation of the Cursive Writing Exploratory Test (PEEC) were used, the results obtained from the test indicate that the case study student presents an academic performance below that expected in the processes normal and fast copy speeds, with a 22nd and 7th percentile, respectively for fast copy speeds. The copy quality process has an 11th percentile below average, which shows graphical errors in the writing process. From the observation of types of errors, served as the basis for building strategies based on the ludic, called "Praxia in a World of Games", in which its effectiveness was verified from the file of achievements that demonstrates progress in the development of the student's writing skills.